A Bibliometric Analysis of Influencer Marketing Research - Mahanta, Deepshikha; Baruah, Uttam Kr. (International Review of Management and Marketing, 2026)
The growth of social media has contributed to the growth of influencer marketing, generating interest among scholars to conduct research on this topic. Thus, a bibliometric analysis was conducted to understand the trend of research in this field by reviewing the documents published in the Scopus database. After screening 2028 documents, 837 documents were identified. The analysis of documents was done by using VOS viewer software. The influencer marketing research peaked in 2020. The most contributing country in this field is the United States of America. Currently, the research in this area is mainly focusing on identifying the factors affecting its effectiveness as a marketing strategy. However, virtual influencer marketing is emerging as a focal point of discussion.